Information and Communication Technologies (Ict) for Knowledge Management - Hales, Colin F. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2007)
This paper deals with the role of Information and Communication Technologies in Development (ICT4D) with special attention to the potential of Open Source Software (OSS) in helping to bridge the Digital Divide. Herein a great amount of emphasis is paid to the role of Open Source Software (OSS) in the important development field of Knowledge Management by their input for improving knowledge management which is seen as a prerequisite to the advancement of the Knowledge Society in developing countries. The objective is to review and discuss the concept of Open Source Software (OSS) and Knowledge Management in the attempt to bridge the Digital Divide.

Praca ta zajmuje się znaczeniem technologii teleinformatycznych (ICT) w zarządzaniu wiedzą. Koncentruje się w szczególności na roli, jaką odgrywa wolne czy darmowe oprogramowanie (F/OSS) w tym procesie. Przedstawia w skrócie niektóre z najbardziej przydatnych oraz popularnych rozwiązań z tego zakresu oraz sposób, w który mogą przyczynić się do poprawy dostępu do narzędzi ICT dla krajów rozwijających się. Celem pracy było omówienie koncepcji OSS oraz roli tych narzędzi w zarządzaniu wiedzą jako sposobie redukowania przepaści cyfrowej.
Rola otwartego oprogramowania (OSS) w zarządzaniu wiedzą